2022
DOI: 10.1186/s12883-022-02575-8
|View full text |Cite
|
Sign up to set email alerts
|

Acute disseminated encephalomyelitis with bilateral optic neuritis following ChAdOx1 COVID-19 vaccination

Abstract: Background Acute disseminated encephalomyelitis (ADEM) is a rare immune-mediated inflammatory demyelinating disease of the central nervous system. We report a case of ADEM presenting with bilateral optic neuritis temporally associated with the ChAdOx1 vaccine against SARS-COVID19 virus. Case presentation A 36-year-old female presented with bilateral optic neuritis following her first dose of the ChAdOx1 vaccine. Initial MRI Brain showed evidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 31 publications
2
30
0
Order By: Relevance
“…We also summarize case reports of COVID‐19 vaccine‐related encephalomyelitis in Table 4 . 8 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 Similar to our case, the symptoms of encephalitis developed within 30 days after vaccination. After excluding alternative causes, vaccination‐related autoimmune encephalitis was suspected and symptoms rapidly recovered after the initiation of immunosuppressive therapy.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We also summarize case reports of COVID‐19 vaccine‐related encephalomyelitis in Table 4 . 8 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 Similar to our case, the symptoms of encephalitis developed within 30 days after vaccination. After excluding alternative causes, vaccination‐related autoimmune encephalitis was suspected and symptoms rapidly recovered after the initiation of immunosuppressive therapy.…”
Section: Discussionsupporting
confidence: 87%
“…Zuhorn et al 18 also reported 3 cases of acute encephalitis after AZ vaccine injection. We also summarize case reports of COVID‐19 vaccine‐related encephalomyelitis in Table 4 8,19–26 . Similar to our case, the symptoms of encephalitis developed within 30 days after vaccination.…”
Section: Discussionsupporting
confidence: 75%
“…In the case of mRNA‐vectored vaccines, it is also possible that the lipid nanoparticles required to prevent enzymatic degradation of mRNA particles may be a trigger for GBS in genetically or environmentally susceptible individuals [ 50 , 51 ]. Also, other neuroimmunological syndromes such as fulminant encephalomyelitis (overlapping with GBS), optic neuritis, and acute disseminated encephalomyelitis as AEFIs have been reported among recipients of SARS‐CoV‐2 vaccines [ 52 , 53 , 54 ]. Still, a causal relationship between anti‐SARS‐CoV‐2 vaccines and GBS is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, none of these patients manifested electrophysiological evidence of a peripheral neuropathy. Nagaratnam et al reported a case of bilateral optic neuritis following a ChAdOx1 COVID-19 vaccination ( Nagaratnam et al, 2022 ). Rodrigo-Armenteros et al reported a case of 62-year-old male, with left eye amblyopia since childhood who presented with asymptomatic left optic neuropathy and a prolonged left P100 latency after a COVID-19 infection (Rodrigo-Armenteros et al, 2021).…”
Section: Evoked Potentials (Eps)mentioning
confidence: 99%